Shulembaeva K.K., Chunetova Zh.Zh., Dauletbaeva S.B., Tokubaeva A.A., Omirbekova N.Ch., Zhunusbaeva Zh.K., Zhusuppova A.I. Selection for resistance of soft wheat adaptability to environmental conditions in the south –east of Kazakhstan: Al-Farabi Kazakh National University, Almaty, Kazakhstan (Eurasian Journal of Ecology, 2018)
This article presents the results of the research dedicated to the production of mutant forms under impact of chemical compounds, in particular cadmium chloride; chromosomal localization of genes, responsiblefor the important signs for selection; obtaining morphologically markedaneuploid lines and reconstruction of the genome of soft wheat with intravarietal replacement chromosomes. As a result of the research the optimum concentration of CdCl2 – 0,01%, solution was found. This solution isresponsible for plants growth and development. Among 10 different sortsof soft wheat only 4 species demonstrate sensitivity to chlorine cadmium– Kazakhstan 3, Zhenis, Shagala, Lyutescens 32. The level of fertility of softwheat hybrids crossed with wild species (t. timopheevii, t. dicoccum и t.kiharae) depends on the direction of crosses and specimen genotype. Wildspecies as a parent component, positively impact on a high percentage oftying grains in specific ecological zones of Kazakhstan. It was checked out,that Nadezhda specie genome is highly compatible with the genomes ofwild species T. timopheevii, T. dicoccum и T. kiharae.Key words: Mutagenesis, isogenic substituted wheat lines, selection,mutant strain